Adjunctive Physiotherapy - A Case Report on the Management and Effective Treatment of Diabetic Neuropathic Foot Ulcer Using Adjunctive Physiotherapy - Coplin M. (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2021)
Physiotherapy must be considered and reprioritized as an adjunctive medical service for long term health and rehabilitation. Comprehensive physiotherapy has the potential to be administered in out-patient rehabilitation facilities, hospitals, and Thermal Health Centers. A review of select adjunctive physiotherapy methods will be presented along with a case report of the successful treatment, with rationally selected physiotherapeutic agents, of a Diabetic Neuropathic Foot Ulcer scheduled for surgical amputation. By highlighting this case, the author is attempting to bring attention to familiar and time-tested therapies that have fallen out of use in a primary intervention context. This case report aims to exemplify that the role for rational physiotherapeutic methods stretches beyond current mainstream applications. Historical Context. Will supply the historical and foundational work in the field of physiotherapy that contextualizes the rational basis for the applications described in the case. Therapies. Lists the physiotherapy methods highlighted in this case, reviews the mechanism of action, discusses the therapeutic application, and provides modern citation for the rationalization of the therapy. Case Report. Reviews a detailed narrative of the case in review. Covers intake, case history, progression of case, as well as clinical applications for physiotherapy as they arise in the course of case management. Conclusion. Reviews the emphasis for reconsidering the role of Physiotherapy in the primary management of acute and chronic illness.